Chapter 12 Chinese media translation - liu, nancy xiuzhi (Taylor & Francis, 2017)
The Routledge Handbook of Chinese Translation presents expert and new research in analysing and solving translation problems centred on the Chinese language in translation. The Handbook includes both a review of and a distinctive approach to key themes in Chinese translation, such as translatability and equivalence, extraction of collocation, and translation from parallel and comparable corpora. In doing so, it undertakes to synthesise existing knowledge in Chinese translation, develops new frameworks for analysing Chinese translation problems, and explains translation theory appropriate to the Chinese context. The Routledge Handbook of Chinese Translation is an essential reference work for advanced undergraduate and postgraduate students and scholars actively researching in this area.